(3GdGSJKeGQGJ aj GdHfhc hGdeDSSGJ GdeGdjIs (3ef efXhQ GOGQj heMGSHjs - (3QRb(B, (3YGOd eMeOs ((3GdbGgQIs (3OGQ WHjI ddfTQ hGdJhRjY hGdJLgjRGJ GdYdejIs, 2004)
(3aj gPG GdcJGH (B: (3ebOeI GdHGH GdChd (B: (3GdGSJKeGQGJ GdeGdjI aj GdHfhc hGdeDSSGJ GdeGdjI GdeTGHgI GdaUd GdChd (B: (3eaghe GdGSJKeGQ aj GdacQ GdeMGSHi hGdEOGQi (B: (3GdaUd GdKGfj (B: (3JMdjd GdOQGSGJ GdSGHbI aj eLGd GdeYGjjQ GdeMGSHjI GdeDKQI Ydi bQQGJ GdGSJKeGQGJ GdeGdjI (B: (3GdaUd GdKGdK (B: (3GdEOGQI GdESJQGJjLjI deNGWQ GdGSJKeGQ (B: (3GdaUd GdQGHY (B: (3GdCOhGJ GdeGdjI GdeHJcQI GdHGH GdKGfj (B: (3CSS Jbjje GdGSJKeGQGJ GdeGdjI GdaUd GdChd (B: (3Jbjje GdGSJKeGQGJ aj VhA eYGjjQ GdeMGSHI GdeUQjI hGdOhdjI hGdGeQjcjI (B: (3GdaUd GdKGfj (B: (3Jbjje GdGSJKeGQGJ GdeGdjI aj GdHfhc aj VhA GdbhGYO GdUGOQI ef GdHfc GdeQcRi GdeUQi (B: (3GdaUd GdKGdK (B: (3GdHfhc GdTGedI hTQcGJ JOGhd GdChQGb GdeGdjI GdHGH GdKGdK (B: (3GdEaUGM aj GdHfhc hGdeDSSGJ GdeGdjI GdeTGHgI GdaUd GdChd (B: (3eJWdHGJ GdEaUGM GdYGOd ddbhGFe GdeGdjI (B: (3GdaUd GdKGfj (B: (3GdEaUGM aj GdHfhc aj VhA eYGjjQ GdeMGSHI hGdbhGYO GdUGOQI ef GdHfc GdeQcRi (B: (3GdaUd GdKGdK (B: (3GdEaUGM Yf GdCOhGJ GdeGdjI GdeHJcQI (B: (3GdaUd GdQGHY (B: (3GdJhUjGJ hGdNdGUI(B.s
Keywords: (3GdGSJKeGQs; (3GdHfhcs; (3GdeMGSHIs